Identifying research priorities for pregnant South Asian immigrants in Canada: A James Lind Alliance approach - Anam Shahil-Feroz; Bibi Hajira; Sugandha Chandak; Salima Meherali; Saraswathi Vedam; Anushka Ataullahjan; Rohan D’Souza (PLoS ONE, 2025)
Background Pregnant South Asian immigrants (PSAI) make up a significant portion of immigrants to Canada and face a higher risk of adverse pregnancy outcomes compared to other ethnic groups. This disparity is largely due to cultural and linguistic barriers to maternity care, including language difficulties, limited cultural sensitivity in healthcare services, and a lack of awareness about culturally tailored educational resources. Despite the growing number of PSAI in Canada, there is limited understanding of how to best support their healthcare and well-being. To address this gap, we aim to conduct a priority-setting exercise to identify key research priorities and establish a patient-oriented research agenda that will drive long-term, impactful research and ultimately improve maternal health outcomes for PSAI in Canada. Methods This project follows the James Lind Alliance (JLA) priority-setting partnership (PSP) methodology, which includes forming a steering committee, identifying and verifying uncertainties, conducting an interim priority-setting phase, and holding a final workshop. Participants will include first-generation South Asian immigrant women from Bangladesh, India, Pakistan, and Sri Lanka, as well as clinicians, researchers, and community/professional organizations from Ontario, Alberta, and British Columbia. Data will be collected through Zoom-based recorded working group sessions and an online ranking survey. Qualitative data will be analyzed using an inductive content analysis approach supported by NVivo software. Subgroup diversity (e.g., ethnicity, gender, age, and geography) will be tracked across participant groups. Consensus on top research priorities will be achieved through a structured ranking process followed by a facilitated virtual workshop. The study began in May 2025 and is expected to conclude by January 2026, a timeline consistent with similar JLA PSP initiatives. Dissemination All findings will be shared through a peer-reviewed publication and conference presentations for the scientific community, a lay summary for community organizations, and a video and infographic for patient participants. Community and professional organizations will also support the dissemination of findings through their networks and social media channels.